A Representation of the Resolvent Operator of Singular Hahn-Sturm-Liouville Problem. (11th March 2020) - Allahverdiev, Bilender P.; Tuna, Hüseyin
Abstract: In this article, we construct the resolvent operator of regular Hahn-Sturm-Liouville problem. Later we derive some properties of the resolvent operator. Finally, we obtain integral representation for the resolvent operator of singular Hahn-Sturm-Liouville problem in terms of the spectral function.